(untitled) (Iraqi Journal of Civil Engineering, 2021)
Recently, COVID-19 pandemic has swept the world left many victims as well as heavy casualties in the global economic system. As a result, governments have applied some necessary actions such as curfew and restricted mobility between cities, in order to control the spread of COVID-19 pandemic. However, these actions can decrease the traffic congestions within megacities leading to cleaner air and lower temperature. On the other hand, these actions have negative impacts on tourism in congested cities like Karbala and Najaf.Nowadays, urban climatic phenomena within holy cities have attracted researchers . The aim of this study is the evaluation of Urban Climate in term of temperature before and during COVID-19 pandemic period by using Landsat images and GIS techniques. Final findings showed a difference between Land surface temperature before and during COVID-19, which reached about 9 C° within built-up areas and bare lands. While this difference showed a relatively slight decrease within vegetated areas and waterbodies reached about 2 C°. This indicated that built-up areas and bare lands have been mainly affected by governmental restrictions during COVID-19 compared to other areas. Our analysis indicated that the temperature of the surface in urban areas has decreased during COVID-19 compared to the period before COVID-19. The proposed method can pave the way for planners and decision-makers to evaluate other holy cities in terms of the environment and recent disasters like the COVID-19 pandemic